Who lives in a pear tree under the sea? A first look at tree reefs as a complex natural biodegradable structure to enhance biodiversity in marine systems - Dickson, Jon; Franken, Oscar; Watson, Maryann S.; Monnich, Bob; Holthuijsen, Sander; Eriksson, Britas Klemens; Govers, Laura L.; van der Heide, Tjisse; Bouma, Tjeerd J. (Frontiers in Marine Science, 2023)
Hard substrates play an important role in global marine systems as settlement surface for sessile reef-forming species such as corals, seaweeds, and shellfish. In soft-sediment systems, natural hard substrates such as stones, bedrock and driftwood are essential as they support diverse assemblages of reef-associated species. However, availability of these hard substrates has been declining in many estuaries and shallow seas worldwide due to human impacts. This is also the case in the Dutch Wadden Sea, where natural hard substrates have gradually disappeared due to burial by sand and/or active removal by humans. In addition, driftwood that was historically imported from rivers has been nullified by upstream logging and coastal damming of estuaries. To investigate the historic ecological role of wood presence in the Wadden Sea as settlement substrate and fish habitat, we constructed three meter high artificial reefs made of felled pear trees. Results demonstrate that these reefs rapidly developed into hotspots of biodiversity. Within six months, the tree-reefs were colonized by sessile hard substrate associated species, with a clear vertical zonation of the settled species. Macroalgae and barnacles were more abundant on the lower parts of the reef, while bryozoans were more dominant on the upper branches. In addition, six fish species were observed on the reefs, while only two species were caught on sandy control sites. Moreover, the abundance of fish on the reefs was five times higher. Individuals of the most commonly caught species, the five-bearded rockling Ciliata mustela, were also larger on the reef. These patterns also hold true for common prawn, Palaemon serratus, which were also larger and ten times more numerous on the reefs. Present findings indicate that the reintroduction of tree-reefs as biodegradable, structurally complex hard substrates can increase local marine biodiversity in soft-sediment systems within relatively short time scales.